PERFORMANCE TEST OF SOLAR CABINET DRYER AND SOLAR TUNNEL DRYER ON DRYING COCOA BEANS - Liefson Jacobus; Suryawirawan Dwiputranto; Rahmat Sentosa Gule; Elyakim Nova Supriyedi Patty (Sean Institute, 2023)
This study aims to compare dryers for cocoa beans. The comparison carried out is a comparison of tools, moisture content, mass, quality of beans, and the time required by each tool in drying. The drying tools used are traditional solar cabinet dryers and solar tunnel dryers. Conventional drying uses direct sun contact on cocoa beans, and solar tunnel dryer uses two types to dry cocoa beans: hot air absorbed by solar collectors and direct sun. In contrast, solar cabinet dryer uses hot air absorbed by solar collectors and driven by fans in the drying room. The research was carried out from 09.00 until 16.00 in 31/2 hours, so in a day, there are three observation data for each research tool. To the research results, the time required for each tool is different, the solar cabinet dryer tool takes four days, and the solar tunnel dryer traditionally takes three days to dry cocoa beans; drying is done 7 hours a day. The highest ambient temperature is up to 36.3oC, the temperature entering the drying chamber for the solar cabinet dryer is up to 54.2oC, and the solar tunnel dryer is up to 51oC. With a mass of 1.5 kg of material dried to 0.50 kilograms, leaving a moisture content of 12%.